Development of a toolkit to improve interprofessional collaboration and integration in primary care using qualitative interviews and co-design workshops - Muhammed Mustafa Sirimsi; Muhammed Mustafa Sirimsi; Hans De Loof; Kris Van den Broeck; Kristel De Vliegher; Paul Van Royen; Peter Pype; Kristel Driessens; Emily Verté; Emily Verté; Roy Remmen; Peter Van Bogaert (Frontiers Media S.A., 2023)
BackgroundDespite numerous attempts to improve interprofessional collaboration and integration (IPCI) in primary care, patients, care providers, researchers, and governments are still looking for tools and guidance to do this more efficiently. To address these issues, we decided to develop a generic toolkit, based on sociocracy and psychological safety principles, to guide care providers in their collaboration within and outside their practice. Finally, we reasoned that, in order to obtain integrated primary care, different strategies should be combined.MethodsDevelopment of the toolkit consisted of a multiyear co-development process. Data originating from 65 care providers, through 13 in-depth interviews and five focus groups were analysed and subsequently evaluated in eight co-design workshop sessions, organised with a total of 40 academics, lecturers, care providers and members of the Flemish patient association. Findings from the qualitative interviews and co-design workshops were gradually, and inductively adapted and transformed into the content for the IPCI toolkit.ResultsTen themes were identified: (i) awareness of the importance of interprofessional collaboration, (ii) the need for a self-assessment tool to measure team performance, (iii) preparing a team to use the toolkit, (iv) enhancing psychological safety, (v) developing and determining consultation techniques, (vi) shared decision making, (vii) developing workgroups to tackle specific (neighbourhood) problems, (viii) how to work patient-centred, (ix) how to integrate a new team member, and (x) getting ready to implement the IPCI toolkit. From these themes, we developed a generic toolkit, consisting of eight modules.ConclusionIn this paper, we describe the multiyear co-development process of a generic toolkit for the improvement of interprofessional collaboration. Inspired by a mix of interventions from in and outside healthcare, a modular open toolkit was produced that includes aspects of Sociocracy, concepts as psychological safety, a self-assessment tool and other modules concerned with meetings, decision-making, integrating new team members and population health. Upon implementation, evaluation and further development and improvement, this compounded intervention should have a beneficial effect on the complex problem of interprofessional collaboration in primary care.